Hedgehog signaling directs cell differentiation and plays a critical role in tendon enthesis healing - Fei Fang; Matthew Casserly; Julia Robbins; Stavros Thomopoulos (npj Regenerative Medicine)
Abstract A high prevalence of rotator cuff tears presents a major clinical challenge. A better understanding of the molecular mechanisms underlying enthesis development and healing is needed for developing treatments. We recently identified hedgehog (Hh)-lineage cells critical for enthesis development and repair. This study revealed cell-cell communication within the Hh-lineage cell population. To further characterize the role of Hh signaling, we used mouse models to activate and inactivate the Hh pathway in enthesis progenitors. Activation of Hh target genes during enthesis development increased its mineralization and mechanical properties. Activation of Hh signaling at the injured mature enthesis promoted fibrocartilage formation, enhanced mineralization, and increased expression of chondrogenic and osteogenic markers, which implies that Hh signaling drives cell differentiation to regenerate the damaged enthesis. Conversely, deletion of Hh target genes impaired enthesis healing. In summary, this study revealed a new strategy for enthesis repair via activation of Hh signaling in endogenous cells.